Energia digestível para reprodutores de Tilápia do Nilo (Oreochromis niloticus) - Bombardelli, Robie Allan (2007)
The present study was carried out to evaluate the reproductive and zootechnical performance, and the lipids deposition in the liver tissue of females and males of-the-Nile tilapia (Oreochromis niloticus L.) fed with diets containing different levels of digestible energy, from the soybean oil inclusion. There were used 400 breeding, being 300 females and 100 males, distributed in a completely randomized design, composed of five treatments and four replications. The breeding were fed with diets containing 35% of crude protein in 2700, 2950, 3200, 3450 and 3700 kcal energy digestível.kg of feed-1, and submitted to the hapas reproductive management with reproductive rest of 12 days. The diets levels of digestible energy offered to breeding did not influence (P>0.05) the spawning females' percentage, fertility, or the eggs and off springs characteristics. The sperm production, the seminal pH, the survival rate and sperm activation time, were not affected (P>0.05) by rations. The zootechnical performance of breeding from both sexes also was not influenced by treatments (P> 0.05).However, the diets containing 3465.56 and 3443.43 kcal energy digestível.kg of feed-1, increased (P<0.05) the spermatic concentration and normality, producing 7.98 x109 sperms.mL per released semen -1 and 38.98% of normal sperm. The diets energy levels also caused an increase (P<0.05) of lipid inclusions in fish hepatocytes of both sexes. The reproductive and zootechnical performance results of females may be associated with the short period of time that the breeding were fed with experimental diets or even the possible reduction of n-3 fatty acids levels in the diet. The reproductive performance improvement of male may be related with the increased metabolic energy available for spermatogenesis and with the increased availability of n-6 fatty acids. Overall, the increasing levels of digestible energy in feed offered to breeding affected only the reproductive performance of males where 3465.56 and 3443.43 kcal energy digestível.kg of feed-1 ensure better and normal sperm concentrations. Moreover, the increasing energy levels in diets promoted, in both sexes the increase in the hepatocytes occupation by lipids.